Anthropology and the study of earthen architecture in South Africa (Acta Academica, 2015)
The contribution of anthropology to the study of shelter in Africa has been found wanting. Social Anthropology in Africa and South Africa in particular has been guilty of this neglect, while scholars from the Volkekunde paradigm have been documenting house, settlement and material culture since the early 1900s. This neglect by anthropology as a discipline could be remedied. The  anthropologist as a fieldworker is ideally positioned to study local knowledge and its manifestations and transfer in the earth building world. Among others the resultant research could contribute to our understanding of how poor people use earthen building knowledge to adapt in changing environments such as informal settlements.